THE APPLICATION OF BLENDED LEARNING WITH CONCRETE MEDIA TO IMPROVE THE ABILITY TO CALCULATE DIVISION IN SD MUHAMMADIYAH 11 SURABAYA - Ira Ratnasari; Deni Adi Putra; Kunti Dian Ayu Afiani (Universitas Trunojoyo Madura, 2022)
This research aims to describe the application of blended learning models with concrete material and describes the improvement of students' learning outcomes in the application of blended learning with concrete media assisted in dividing materials. This research is a class action research (PTK). The subject of the study was a 2nd grade of Al Alaq Sd Muhammadiyah 11 Surabaya. The results of this study are (1). Research is carried out in two cycles, where each cycle has four steps, namely planning, implementation, observation and reflection. (2). Increase in learning outcomes ranging from pre-cycle by 60.5, cycle 1 by 70.6, cycle 2 by 86.7 and Percentage of classical completion in pre-cycle by 33.3%, cycle 1 by 66.7% included in sufficient category, cycle 2 to 83.3% belongs to good category. From the results of the research obtained, it was concluded that the blended learning model with concrete media can improve the learning outcomes of students in the 2nd grade of Al-Alaq SD Muhammadiyah 11 Surabaya. This research can be utilized by elementary school teachers as a reference to improve the learning outcomes of 2nd grade students on division materials.